Translation Techniques of Islamic Terminology in CM Hizboel Wathony’s Musibah adalah Anugerah (A Blessing in Disguise) - Mediyani Budiyanto (MOZAIK HUMANIORA, 2022)
This study aims to identify translation techniques used in translating Islamic and tawheed terminology in the book entitled Musibah adalah Anugerah (A Blessing in Disguise) by Syech Maulana Hizboel Wathony Ibrahim. This study is an annotated translation from L1 to L2. Annotated translation is a translation supported by annotations or the translator’s commentary on the chosen equivalents. To pursue the aim of this study, qualitative method is used together with library research design. This study then finds out that the translation of Islamic and tawheed terminology presents an array of translation problems. One of the problems is that there is no direct equivalent properly conveying the meaning stated in the ST (source text). For that reason, substantial schematic knowledge is required in order to fully grasp the ST and to choose the most accurate equivalent. In addition, a thorough understanding in regard to translation technique is also vital in order to select an accurate equivalent properly. Some techniques often used are transposition, modulation, generalization, couplet, and triplet. However, modulation translation technique is mostly used in translating Islamic and tawheed terminology in the book entitled Musibah adalah Anugerah (A Blessing in Disguise).